A finite element method for Allen–Cahn equation on deforming surface. (15th May 2021) - Olshanskii, Maxim; Xu, Xianmin; Yushutin, Vladimir
Abstract: The paper studies an Allen–Cahn-type equation defined on a time-dependent surface as a model of phase separation with order–disorder transition in a thin material layer. By a formal inner–outer expansion, it is shown that the limiting behavior of the solution is a geodesic mean curvature type flow in reference coordinates. A geometrically unfitted finite element method, known as a trace FEM, is considered for the numerical solution of the equation. The paper provides full stability analysis and convergence analysis that accounts for interpolation errors and an approximate recovery of the geometry.